Anterior Cingulate Cortex Glutamate Levels Are Related to Response to Initial Antipsychotic Treatment in Drug-Naive First-Episode Schizophrenia Patients - Li, Jinguang; Ren, Honghong; He, Ying; Li, ZongChang; Ma, Xiaoqian; Yuan, Liu; Ouyang, Lijun; Zhou, Jun; Wang, Dong; Li, Chunwang; Chen, Xiaogang; Han, Hongying; et al. (Frontiers in Psychiatry, 2020)
The glutamatergic systems have previously been shown to be involved in the pathophysiology of schizophrenia and the mechanisms of action of antipsychotics treatment. The aim of present study was to investigate the relationship between levels of glutamate (Glu) or Glu/total creatine (Glu/Cr+PCr) in the anterior cingulate cortex (ACC) and the psychiatric symptoms and response to antipsychotic treatment. We performed proton magnetic resonance spectroscopy(1H–MRS) to measure Glu and Glu/Cr+PCr in ACC of 35 drug-naive first-episode schizophrenia (FES) patients and 40 well matched health controls (HC). After scanning, patients were treated with risperidone for 8 weeks. Remission status was based on Positive and Negative Syndrome Scale (PANSS) scores at week8.At baseline, there were no significant differences on levels of Glu or Glu/Cr+PCr in ACC between drug-naïve FES and HC. Lower baseline levels of Glu and Glu/Cr+PCr in ACC associated with more severe negative symptoms of schizophrenia. Compared to remission group (RM), non-remission group (NRM) had a lower baseline ACC Glu levels (P<0.05).Our results suggest that ACC Glu levels may be related to the severity of symptoms in the early stages of schizophrenia, and therefore may be used as a marker to evaluate treatment effect of antipsychotics in schizophrenia patients.